Stress-Induced Enhanced Long-Term Potentiation and Reduced Threshold for N-Methyl-D-Aspartate Receptor- and β-Adrenergic Receptor-Mediated Synaptic Plasticity in Rodent Ventral Subiculum - Bartsch, Julia C.; von Cramon, Monique; Gruber, David; Heinemann, Uwe; Behr, Joachim (Frontiers in Molecular Neuroscience, 2021)
Stress is a biologically relevant signal and can modulate hippocampal synaptic plasticity. The subiculum is the major output station of the hippocampus and serves as a critical hub in the stress response network. However, stress-associated synaptic plasticity in the ventral subiculum has not been adequately addressed. Therefore, we investigated the impact of a single exposure to an inherently stressful two-way active avoidance conditioning on the induction of long-term potentiation (LTP) at CA1 – subiculum synapses in ventral hippocampal slices from young adult rats one day after stressor exposure. We found that acute stress enhanced LTP and lowered the induction threshold for a late-onset LTP at excitatory CA1 to subicular burst-spiking neuron synapses. This late-onset LTP was dependent on the activation of β-adrenergic and glutamatergic N-methyl-D-aspartate receptors and independent of D1/D5 dopamine receptor activation. Thereby, we present a cellular mechanism that might contribute to behavioral stress adaptation after acute stressor exposure.